(untitled) (Revista de Ciências Agroveterinárias, 2019)
This study aimed to test the efficiency of the Melia azedarach supercritical extract in controlling Sitophilus zeamais through tarsal contact. The survival of insects was observed every 24 h after the experiment started. A higher mortality of insects was found during the first 72 h. The treatment that had the best performance considering the action time and the number of dead insects was that at 200 μL mL-1 concentration. The mean lethal concentration that kills 50% of the population (LC50) obtained after 96 h treatment was 165.52 µL ml-1, showing that the higher dose can be reduced with satisfactory results for the conditions used in this study. The extract of M. azedarach was effective in controlling S. zeamais under laboratory conditions.